ASSOCIATION OF ADRA2B POLYMORPHISM WITH RISK FACTORS FOR CARDIOVASCULAR DISEASES IN NATIVE POPULATION OF MOUNTAIN SHORIA - T. A. Mulerova; A. Yu. Yankin; Ye. V. Rubtsova; A. A. Kuzmina; P. S. Orlov; N. P. Tatarnikova; V. N. Maksimov; M. I. Voevoda; M. Yu. Ogarkov (Бюллетень сибирской медицины)
Study objectives: examine the frequency of genotypes and alleles of I/D polymorphism of gene ADRA2B of native people living in Mountain Shoria (the Shors), as well as their association with risk factors for cardiovascular diseases.Material and methods. Overall 221 native people of Shoria were examined. The average age is51.07 ± 1.46 among males, 52.93 ± 0.96 among females (p = 0.286). Anthropometric characteristics, lipid levels of blood and I/D polymorphism of ADRA2B were studied.Results. DD genotype of the gene ADRA2B in the native population of the Shor people is associated with adiposis and high index of "waist/hip", hypertriglyceridemia. The average values of Quetelet index is higher in carriers of this genotype compared with carriers of genotype ID. Average waist indications in homozygous insertions were lower than those in homozygous deletions and heterozygotes. Patients with genotype DD have higher average levels of triglycerides, atherogenic index, cholesterol, very low density lipoproteins.Conclusion. DD allele ADRA2B genotype is responsible for adiposis and high levels of TG among native population of Shoria.